Evaluation of the readability, understandability, and actionability of COVID-19 public health messaging in Atlantic Canada - Kelly, Katherine Jennifer; Campbell, Alyson; Salijevic, Anja; Doak, Sarah; Michael, Laurie; Montelpare, William (Frontiers in Communication, 2023)
Effective communication of COVID-19 information involves clear messaging to ensure that readers comprehend and can easily apply behavioral recommendations. This study evaluated the readability, understandability, and actionability of public health resources produced by the four provincial governments in Atlantic Canada (New Brunswick, Newfoundland and Labrador, Nova Scotia, and Prince Edward Island). A total of 400 web-based resources were extracted in June 2022 and evaluated using the Flesch-Kincaid Grade Level, CDC Clear Communication Index, and the Patient and Education Materials Assessment Tool. Descriptive statistics and a comparison of mean scores were conducted across provinces and type of resources (e.g., text, video). Overall, readability of resources across the region exceeded recommendations, requiring an average Grade 11 reading level. Videos and short form communication resources, including infographics, were the most understandable and actionable. Mean scores across provinces differed significantly on each tool; Newfoundland and Labrador produced materials that were most readable, understandable, and actionable, followed by New Brunswick. Recommendations on improving clarity of COVID-19 resources are described. Careful consideration in the development of publicly available resources is necessary in supporting COVID-19 knowledge uptake, while reducing the prevalence of misinformation.